Association analysis for grain quality traits in rice - Verma, Harendra; Pathak, K.; Rathi, S.; Sarma, R.N. (The Indian Journal of Genetics and Plant Breeding, 2016)
Association analysis was conducted on a panel of accession of indigenous rice using SSR markers for nine traits related to grain and cooking quality parameters of rice. The value of PIC ranged from 0.316 (RM21945) to 0.738 (RM252) with an average of 0.505 for all the genotypes under study. A previously identified marker linked to amylose content, RM 190 on chromosome 6, showed a strong association for amylose content in this class of rice. Another marker on chromosome 7, RM11, also showed an association with amylose content. Two markers (RM169 and RM21945 with two alleles) showed associations with gel consistency. Four significant associations for gelatinization temperature were detected by four markers (RM11, RM12, RM21 and RM169). A total of six associations were detected for grain length, by five markers. For decorticated grain length 12 number of association was detected by seven markers. For grain length after cooking 11 associations were detected by six markers. Two associations were detected for grain width. Four associations were detected for decorticated grain width by three markers. Two associations were detected for grain width after cooking on chromosomes 4 and 5. The present study also validated the two linked markers, RM21936 for grain length and RMw513 for grain length after cooking, for use in MAS. The study indicates the presence of novel QTLs for a few traits under consideration. The study reveals the feasibility of undertaking association analysis in conjunction with germplasm characterization